2005
DOI: 10.1111/j.1096-0031.2005.00066.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic analysis of Themira (Sepsidae: Diptera): sensitivity analysis, alignment, and indel treatment in a multigene study

Abstract: In this study we use sensitivity analysis sensu Wheeler (1995) for a matrix entirely composed of DNA sequences. We propose that not only congruence but also phylogenetic structure, as measured by character resampling, should be used to choose among competing weighting regimes. An extensive analysis of a five-gene data set for Themira (Sepsidae: Diptera) reveals that even with different ways of partitioning the data, measures of topological congruence, character incongruence, and phylogenetic structure favor si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 77 publications
1
32
0
Order By: Relevance
“…However, in the current analysis we go beyond Laamanen et al. (2005) and other studies comparing alignment algorithms (Terry and Whiting, 2005) in that we compare three different alignment strategies: ClustalX (default parameters), Direct Optimization (POY), and “manual” alignment.…”
Section: Comparing Alignment Techniques Through a Sensitivity Analysismentioning
confidence: 99%
“…However, in the current analysis we go beyond Laamanen et al. (2005) and other studies comparing alignment algorithms (Terry and Whiting, 2005) in that we compare three different alignment strategies: ClustalX (default parameters), Direct Optimization (POY), and “manual” alignment.…”
Section: Comparing Alignment Techniques Through a Sensitivity Analysismentioning
confidence: 99%
“…The purpose of this paper is to clarify our different points of view regarding: (1) the meaning of test in science, (2) the relationship of this method of sensitivity analysis to the other methods of data exploration discussed by Giribet (2003a), (3) stability as a scientific goal of phylogenetic inference and (4) the validity of this approach to sensitivity analysis as advancing objective knowledge claims. Because some authors appear unaware of the criticisms of this method of sensitivity analysis (e.g., Laamanen et al., 2005; Worsaae, 2005), as background we begin with a summary of our views on the evaluation of methods of data exploration.…”
mentioning
confidence: 99%
“…The species is morphologically distinct from other sepsids, based on the following male characters: (1) 4 th sternite heavily spinose, (2) syn-sternite 7+8 absent, (3) epandrium enlarged, and (4) hypandrium firmly attached to syntergite 7+8 at one point (Pont 1987). Subsequent phylogenetic research (Zhao et al 2013, Su et al 2008, Laamanen et al 2005, Pont and Meier 2002) showed that this morphological distinctness is associated with a similarly distinct phylogenetic position on the phylogenetic tree of Sepsidae: Zuskamira inexpectata is not nested within any other sepsid genus, and behaves like a "wildcard" taxon whose actual placement on the sepsid phylogeny remains unclear because different topologies are supported by the same data depending on how the data are analyzed (Zhao et al 2013). …”
Section: Introductionmentioning
confidence: 99%